Analisis Manajemen Risiko pada Pengelolaan Operasional UMKM Fotocopy Maju Jaya di Kota Bogor - Ai Malita Wulandari; Intan Nur’aini; Nayla Rubayyina Nugraha; Nuri Triani Anggraeni; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze risk management within the operational activities of the Fotocopy Maju Jaya micro-enterprise using a 3×3 risk matrix through the stages of risk identification, analysis, evaluation, and treatment. Employing a qualitative descriptive approach supported by observations and interviews, the study identifies 28 risks that fall into six categories: market, marketing, financial, operational, human resources, and legal risks. The evaluation using the 3×3 matrix indicates that one risk is categorized as high, twelve risks as medium, and fifteen as low. The highest risk concerns the absence of a routine service schedule for photocopy machines, which may interrupt operations during peak periods. Medium-level risks are mainly related to the absence of standard operating procedures, limited employee skills, unstable cash flow, and insufficient promotional activities. The findings highlight that operational continuity depends heavily on equipment maintenance, workforce competence, and structured procedures. The study recommends implementing routine maintenance, establishing clear SOPs, enhancing employee training, digitizing financial recording systems, and completing business legality requirements to improve operational performance and support the sustainability of Fotocopy Maju Jaya